Imported Chikungunya Virus Strains, Taiwan, 2006–2014 - Yang, Cheng-Fen (Emerg Infect Dis, 2016)
We identified 78 imported chikungunya cases in Taiwan during 2006–2014. Sixty-six (84.6%) cases were initially suspected to be dengue, which indicates the necessity for laboratory diagnostics in differentiation between dengue and chikungunya. Results also emphasize the need for active surveillance of febrile illness at points of entry.